2021
DOI: 10.1088/1755-1315/875/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Plant species selection and biomass nutrient content on post-mine sites of the Kursk magnetic anomaly, Russia

Abstract: The article presents data on the assessment of the different tree and shrubs species for a reclamation of the hydraulic dump of the Kursk Magnetic Anomaly, Russia. The purpose of the work is to identify highly productive tree and shrub species with the maximum content of nitrogen and ash elements in the biomass. The objects of research are protective plantations of Robinia pseudoacacia L., Caragana arborescens L., Betula pendula L., Hippophae rhamnoides L., Pínus sylvestris L., Populus balsamifera L. Under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies in Kazakhstan's neighboring countries have found that vegetation on dumps naturally regenerates in a pattern similar to primary succession, which is the process of plant colonization on a previously unvegetated area. These studies provide valuable insights for post-mined reclamation in Kazakhstan (Shandala et al 2016;Belov et al 2020;Korniyenko et al 2020;Khismatullin et al 2021;Klimova et al 2021;Tchoroev 2021;Treschevskaya et al 2021;Edelev et al 2022;Henyk et al 2022;Chaplygina et al 2023).…”
Section: Introductionmentioning
confidence: 97%
“…Studies in Kazakhstan's neighboring countries have found that vegetation on dumps naturally regenerates in a pattern similar to primary succession, which is the process of plant colonization on a previously unvegetated area. These studies provide valuable insights for post-mined reclamation in Kazakhstan (Shandala et al 2016;Belov et al 2020;Korniyenko et al 2020;Khismatullin et al 2021;Klimova et al 2021;Tchoroev 2021;Treschevskaya et al 2021;Edelev et al 2022;Henyk et al 2022;Chaplygina et al 2023).…”
Section: Introductionmentioning
confidence: 97%